Phytochemical screening of Acacia nilotica extract: an in vitro study - Bhat, Padma K.; Byakod, Abhilasha S.; S. G. , Sushma (International Journal Of Community Medicine And Public Health, 2023)
Background: The present study aim was to identify the presence of phytochemical screening of flower extract of Acacia nilotica. Methods: The flower extract of Acacia nilotica was prepared using Soxhlet apparatus. The preliminary phytochemical analysis of methanol flower of Acacia nilotica was carried out by using simple chemical tests and compared with ethanol and aquesous extract of the same plant. The antimicrobial testing was done using agar well diffusion method. Minimum inhibitory concentration (MIC) was carried out by micro dilution assay and minimum bactericidal concentration (MBC) was done using colony forming unit (CFU) method. SPSS version 20 was used for statistical analysis. Results: The results of phytochemical screening of methanol flower extract of Acacia nilotica showed the presence of alkaloid, flavonoid, glycosides, tannin, terpenoids, steroids whereas ethanol shows the presence of flavonoid, glycosides, tannin, terpenoids, saponin, steroids and aqueous extract shows presence of alkaloid, flavonoid, glycosides, tannin, terpenoids, saponin, steroids. The antibacterial activity of the (flower) extract of Acacia nilotica showed relatively high zone of inhibition (21 mm,19 mm) at 40 mg/ml against S. mutans and L. acidophillus. The MIC OD at 600 nm showed maximum inhibition at 40 mg/ml against S. mutans and L. acidophillius was about 78% and 91% respectively. Conclusions: The present study signifies the phytochemical screening of Acacia nilotica which could be considered in the evolution of an indigenous herbal mouth rinse or toothpaste as the formulation inhibited all the micro-organisms tested in this study at low concentrations.